How Does AI Support Real-World Evidence Generation? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
In the ever-evolving landscape of healthcare, the generation and utilization of Real-World Evidence (RWE) has emerged as a cornerstone for informed decision-...
Keywords: Drug Discovery and Pharmaceutical AI; Support; Real-World; Evidence; Artificial Intelligence; Machine Learning; Deep Learning